â€œIMPLEMENTASI PRAKTIK DENDA PADA PEMBIAYAAN KREDIT PEMILIKAN RUMAH (KPR) AKAD MURABAHAH BERDASARKAN FATWA DSN-MUI NO 17 TAHUN 2000â€ (Studi Kasus BTN Syariah Cabang Yogyakarta) - Ii Sariah (EPI 16 UMY 075, 2016)
According to decision of DSN MUI No.17 2000 that fine is only charged to customers who porposely postpone the payment, and the fund of that fine can not be included into the income of the bank, but rather for social funds. Based on the former research that in BTN Sharia bank of Yogyakarta branch put the fine fund as the income of the bank. This study aims to determine the fine mechanism practice implementation in mortgages (credit of house ownership) in Bank Tabungan Negara Syariah of Yogyakarta branch whether it has already based on the decision of DSN MUI or not yet, how are the management of the funds and where the fund will be channeled. This research is a descriptive research by using the qualitative method. This research is a field research, the data used in this research is the primary data and secondary data which is from Bank Tabungan Negara Syariah Yogyakarta branch. The primary data in this research is obtained by interview with staffs from collection and workout, financing service and marketing. The secondary data is obtained by the library research, the data related to the decision of DSN MUI and official document from Bank Tabungan Negara Syariah of Yogyakarta branch. The result of the research shows that the fine mechanism practice implementation in Bank Tabungan Negara Syariah of Yogyakarta branch in the perspective of regulations and decision which are implemented have been appropriated with the principle and decision of DSN. But the is still misunderstanding in term of fine that should be implemented, Bank Tabungan Negara Syariah uses term "ta'widh' to give fine to customer who are late in payment, in which ta'widh meant by is ta'zir. The management of fund resulted from ta'zir is included into a charity fund, the funds are managed by accomodated system in the head of charity fund channeled to the social charities. Keywords: Murabahah financing, Murabahah fine, decision of DSN MUI